Elevated Membrane and Soluble CD64: A Novel Marker Reflecting Altered FcγR Function and Disease in Early Rheumatoid Arthritis That Can Be Regulated by Anti-Rheumatic Treatment - Matt, Peter; Lindqvist, Ulla; Kleinau, Sandra (PLOS ONE, 2015)
Objectives Fc receptors (FcR) interacting with immune complexes (ICs) is a central event in the immune pathogenesis of rheumatoid arthritis (RA). Here we asked if a specific FcR is linked to RA pathogenesis and if FcR activities relate to disease and treatment outcome in early RA. Material and Methods Twenty autoantibody-positive RA patients and 33 HC were included. The patients were evaluated before and after treatment with methotrexate and prednisolone. At follow-up, the EULAR response criteria were applied to determine the individual treatment outcomes. Serum immunoglobulin levels were measured and the expression of FcR for IgG (FcγR) and IgA (FcαR) on peripheral blood monocytes were determined by flow cytometry. The monocytic FcγR function was evaluated by human IgG1 and IgG3 IC-binding and TNFα stimulated release. Plasma levels of soluble FcRs (sFcRs) were determined with ELISA. Results The IgG1 and IgG3 levels were elevated in the RA sera. The RA monocytes expressed more CD64 and cell surface-bound IgG than HC monocytes, and showed an impaired FcγR function as reflected by changes in IC-binding and decreased IC-stimulated TNFα secretion. These findings correlated significantly with different disease activity markers. Furthermore, sFcRs were elevated in the patient plasma, and sCD64 was specific for RA (compared with a reference group of patients with active psoriatic arthritis). Following treatment, immunoglobulins and sFcR levels were reduced, whereas membrane CD64 was only decreased in patients with good response to treatment. Conclusions Early RA patients display increased membrane and soluble CD64 and an impaired FcγR function correlating with joint disease activity. Beneficial responses of anti-rheumatic treatment in patients reduce CD64. These data suggest sCD64 as an important objective biomarker in RA.